Assessment of Hemodynamic Changes and Complications Occurring with Propofol and Etomidate during General Anesthesia - Singh, Yashovardhan; Varshney, Rohit Kumar; Keshri, Ravi Kumar; Jheetay, G S (Academia Anesthesiologica International, 2019)
Background: Among general anesthesia induction drugs, etomidate is the only imidazole, and it has the most favorable therapeutic index for single bolus administration. Propofol has been shown in clinical studies to be a safe, effective, hypnotic, and amnesic anesthetic agent at induction doses of 2-2.5 mg/kg and maintenance doses of approximately 9mg/kg per hour. Hence; we assessed hemodynamic changes and complications occurring with Propofol and Etomidate during general anesthesia. Subjects and Methods: A total of 100 subjects were enrolled in the present study and were broadly and randomly divided two study groups with 50 subjects in each group: Group A: Subjects who received 1% Propofol injection, and Group B: Subjects who received 0.3mg/kg of etomidate injection. Monitoring of the blood pressure, mean arterial pressure and heart rate was done throughout the surgery and until 10 minutes after induction. Recording of the pain during injection was done on a scale of 0 to 10 with 0 referring to no pain while 10 referring to maximum pain. Results: No significant difference was observed while comparing the mean arterial pressure and heart rate among subjects of both the study groups at different time intervals except for at the time of induction. Mean pain score was found to be significantly higher in group A in comparison to group B. Conclusion: Among patients with associated altered hemodynamic status, etomidate is an improved option. However; further studies are recommended.